2020
DOI: 10.1101/2020.04.22.055590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-dependent correlated segments in the intrinsically disordered region of ChiZ

Abstract: Intrinsically disordered proteins (IDPs) account for a significant fraction of any proteome and are central to numerous cellular functions. Yet how sequences of IDPs code for their conformational dynamics is poorly understood. Here we combined NMR spectroscopy, small-angle X-ray scattering (SAXS), and molecular dynamics (MD) simulations to characterize the conformations and dynamics of ChiZ1-64. This IDP is the N-terminal fragment (residues 1-64) of the transmembrane protein ChiZ, a component of the cell divis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(57 citation statements)
references
References 90 publications
(92 reference statements)
5
52
0
Order By: Relevance
“…In full-length ChiZ (ChiZ-FL), NT is followed by a 21-residue transmembrane helix; on the periplasmic side, a C-terminal LysM domain (residues 113–165) is connected to the transmembrane helix by a 26-residue linker ( Figure 1 ). In a previous study, 20 we showed that, in solution, the NT-only construct ChiZ1-64 is fully disordered without detectable α-helix or β-sheet formation, but with polyproline II (PPII) formation and intramolecular interactions including salt bridges concentrated in the first half of the sequence. Here, we investigated NT-membrane association by solution NMR in the context of ChiZ1-64 and by solid-state NMR on both ChiZ1-64 and ChiZ-FL.…”
Section: Introductionmentioning
confidence: 94%
“…In full-length ChiZ (ChiZ-FL), NT is followed by a 21-residue transmembrane helix; on the periplasmic side, a C-terminal LysM domain (residues 113–165) is connected to the transmembrane helix by a 26-residue linker ( Figure 1 ). In a previous study, 20 we showed that, in solution, the NT-only construct ChiZ1-64 is fully disordered without detectable α-helix or β-sheet formation, but with polyproline II (PPII) formation and intramolecular interactions including salt bridges concentrated in the first half of the sequence. Here, we investigated NT-membrane association by solution NMR in the context of ChiZ1-64 and by solid-state NMR on both ChiZ1-64 and ChiZ-FL.…”
Section: Introductionmentioning
confidence: 94%
“…1). In a previous study 20 , we showed that, in solution, the NT-only construct, ChiZ1-64, is fully disordered without detectable α-helix or b-sheet formation, but with polyproline II (PPII) formation and intramolecular interactions including salt bridges concentrated in the first half of the sequence. Here we investigated NT-membrane association by solution NMR in the context of ChiZ1-64 and by solidstate NMR on both ChiZ1-64 and ChiZ-FL.…”
Section: Very Few Fuzzy Complexes Between Disordered Proteins and Memmentioning
confidence: 96%
“…Association is indicated by loss of crosspeaks due to line broadening from the slow tumbling when a residue interacts with a liposome. Relative to the 1 H-15 N HSQC spectrum of ChiZ1-64 in solution (hereafter "unbound" ChiZ1-64) 20 , no major loss in NMR signals was detected when the liposomes contained POPC only ( Fig. 2a), 4:1 DOPC:DOPE (Fig.…”
Section: Chiz1-64 Associates With Acidic Membranes But Terminal Residmentioning
confidence: 98%
See 2 more Smart Citations